Regenerative Effect of a ROCK Inhibitor, Y-27632, on Excitotoxic Trauma in an Organotypic Culture of the Cochlea - Koizumi, Yutaka; Ito, Tsukasa; Mizutari, Kunio; Kakehata, Seiji (Frontiers in Cellular Neuroscience, 2020)
In the past, most inner ear diseases were thought to start with impairment of the sensory epithelium of the cochlea that progressed subsequently to secondary neural degeneration. However, recent studies show that loss of primary synapses accompanied by excitotoxic degeneration of peripheral axons is likely to be the underlying pathology in sensorineural hearing loss. Rho-associated coiled-coil containing protein kinase (ROCK) inhibition has been reported to have neuroprotective and regenerative effects on synaptic pathways. Therefore, we analyzed the effect of ROCK inhibition using Y-27632 in a model of peripheral axonal damage in the spiral ganglion neurons created using the glutamate agonists, NMDA and kainic acid, to induce excitotoxic trauma in the explanted cochlea. The number of axons projecting to hair cells in the cochlea treated with Y-27632 was significantly greater than those in the cochlea treated only with NMDA + kainic acid. Furthermore, there was a significant increase in synapses between the spiral ganglion and the inner hair cells in the cochlea treated with Y-27632. The findings of this study suggest that ROCK inhibition could be a potential strategy for regeneration of peripheral axons in the spiral ganglion and synapse formation in the inner hair cells of a cochlea that has sustained excitotoxic injury, which is one of the primary etiologies of inner ear disease.